The Influence of Principal Leadership and Organizational Culture on The Work Commitment of Public High School Teachers - Rudi Pranata; Syahril Syahril (Green Publisher Indonesia, 2023)
This research is motivated by the author's observations regarding the influence of the principal's leadership and organizational culture on the work commitment of teachers at SMA Negeri Pasaman Barat which shows that the principal's leadership and organizational culture are still not good and teacher work commitment is still low. The purpose of this study was to obtain data and information about (1) the positive influence of the principal's leadership on the work commitment of teachers of West Pasaman District Senior High School, (2) the positive influence of organizational culture on the work commitment of teachers of West Pasaman District Senior High School, and (3) The influence of positive leadership of the principal and organizational culture on the work commitment of West Pasaman Regency State Senior High School teachers. This research is a correlational quantitative research with associative type. The results of the data analysis show that there is a significant influence between the principal's leadership on teacher work commitment with tcount>ttable (2.578>1.660). There is a significant influence between organizational culture and teacher work commitment with tcount>ttable (6.937>1.660). There is a significant influence between the principal's leadership and organizational culture on teacher performance with a value of Fcount>Ftable (40.629 > 3.09), so there is a significant influence between the principal's leadership and organizational culture together on teacher work commitment. The regression table shows a constant value of 32.864 and a regression coefficient of the X1 variable of 0.263 and a regression coefficient of the X2 variable of 0.646